2021
DOI: 10.3389/fmolb.2020.593976
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serum Metabolomics in Distinguishing Chronic Rhinosinusitis With Nasal Polyp Phenotypes

Abstract: Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a heterogeneous disease characterized by different clinical features and treatment responsiveness. This study aimed to compare the serum metabolomics profiles between eosinophilic CRSwNP (eCRSwNP) and non-eosinophilic CRSwNP (neCRSwNP) and healthy controls (HC) and explore objective biomarkers for distinguishing eCRSwNP before surgery.Methods: Serum samples were collected from 33 neCRSwNP patients, 37 eCRSwNP patients, and 29 HC. Serum metabolomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…The diagnosis of eCRSwNP and neCRSwNP was conducted as previously described: eCRSwNP was defined when the percentage of tissue eosinophils was > 10% of the total inflammatory cells; otherwise neCRSwNP was diagnosed. 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of eCRSwNP and neCRSwNP was conducted as previously described: eCRSwNP was defined when the percentage of tissue eosinophils was > 10% of the total inflammatory cells; otherwise neCRSwNP was diagnosed. 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of eCRSwNP and neCRSwNP was conducted as previously described: eCRSwNP was defined when the percentage of tissue eosinophils was > 10% of the total inflammatory cells; otherwise neCRSwNP was diagnosed. 20,21 rescue regimen of antibiotics and oral steroids, and endoscopic evidence was obtained during outpatient clinic follow-up as previously described. 22,25,26 Serum ALCAM Level Detection Non-anticoagulant peripheral venous blood samples were collected from CRSwNP patients and HCs preoperatively and stored at room temperature for 1-2 hours.…”
Section: Endotyping Crswnpmentioning
confidence: 99%
“…Principal component analysis (PCA) and orthogonal partial least square-discriminant analysis (OPLS-DA) models were used to explore the metabolic difference between the groups. Variable importance for project (VIP) values were applied to evaluate the metabolite’s contribution, and metabolites with VIP >1.0 and p -values <0.05 were regarded as potential biomarkers ( Xie et al, 2020b ). Volcano plot and heat map were generated to exhibit the metabolic regulations of the remarkable changes between different groups ( Wu et al, 2022b ; Roverso et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic rhinosinusitis (CRS) is a common disease characterized by chronic sinonasal mucosal inflammation [ 1 ]. Recent epidemiological studies reported that CRS affected approximately 5.5–28% of the global population, and the prevalence continues to increase [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%